(3GdeMGSHI Yf JcGdja GdYbhO WhjdI GdGLd (B((3GdebGhdGJ(B) /s - (3YWjI, gGTe GMeOs; (3eMeO, eMeO eMehO YHO QHg s ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2002)
(3WHjYI hNUGFU WQjbI JcGdja GdYbhO , fXGe GdeMGSHI Yf JcGdja GdYbhO , GdeMGSHI Yf JcdaI GdehGO , GdeMGSHI Yf JcdaI GdYed GdHTQj , GdeMGSHI Yf JcdaI GdYed GdCdj , GdeMGSHI Yf JcdaI GdYbhO ef GdHGWf , GdeMGSHI Yf GdfabGJ GdYGeI , bjGS GdCQHGM aj fTGW GdebGhdGJs
(3HjHdjhZQGajG (B:(3U(B.183s
Keywords: (3GdJcGdja GdeYjGQjIs; (3GdYbhOs; (3GdeMGSHIs